Ketamine effect on intracellular and mitochondrial calcium mobilization - Bustamante, Jaunita (2016)
The suppressive effects of ketamine on intracellular calcium has been reported in a variety of cells although the mechanisms involved are not well understood. The aim of this work was to evaluate the ketamine effect on the mitochondrial Ca2+  accumulation and the cellular Ca  mobilization using FLUO4-AM and flow cytometry. The results showed that mitochondria from ketamine injected animals presented a lower ability to retain calcium at concentrations higher than 20 μM, as compared with controls (saline injected animals). In addition, ketamine showed a significant decreased KCl-induced intracellular calcium concentration. KCl increased calcium influx through cellular depolarization. According to the data presented herein, ketamine presents a clear inhibitory effect on cytosolic Ca2+  transport mechanisms, independently from their action on the calcium channel associated NMDA receptor.